SINTESIS DODEKIL KLORIDA DARI REAKSI KLORINASI DODEKANOL DENGAN POSFOR TRIKLORIDA - Aritonang, Henry (Sam Ratulangi University, 2009)
Synthesis of dodecyl chloride produced by chlorination reaction of dodecanol with phosphor trichloride was14,48 grams (70,81%). Product of dodecyl chloride was identified by IR spectrometry which shows strongabsorption at 1425-1415 cm-1indicating vibration of group C-Cl and this vibration was supported at 850-600 cm-1 Keywords : dodecyl chloride, chlorination, dodecanol, phosphor trichloride